Role of antioxidant protection system in development of detachment in athletes - A. V. Elikov; M. M. Korosteleva (National Electronic Information Consortium (NEICON), 2022)
Objective: to study the main indicators of free radical oxidation and antioxidant protection in the blood plasma of former athletes, depending on the period of cessation of sports.Materials and methods: 24 former male athletes aged 19‒29 years were examined, who were divided into 2 groups of 12 people each (1st group - former athletes who stopped training for up to 2 years; 2nd - over 2 years). The control group consisted of 15 practically healthy untrained student volunteers of the same age. To study the state of free radical oxidation, we used the determination of the content of active products of thiobarbituric acid by reaction with thiobarbituric acid, spectrophotometrically at a wavelength of 535 nm. Determination of diene conjugates was carried out in the heptane phase after preliminary extraction with a heptane-isopropanol mixture at a wavelength of 233 nm.Results: the direction of the shifts in the state of the oxidative balance was established depending on the period of detraining. The concentration of malondialdehyde in former athletes of the 1st group increased by 38.6 %. In the study of the content of diene conjugates, the staging of changes in the studied indicator was established with the maximum values in the former athletes of the 1st group and lower in the 2nd, exceeding the value of this indicator in the control group by 8.0 %.Conclusions: the obtained data can be recommended for monitoring the state of athletes who stopped playing sports and taken into account when prescribing rehabilitation measures for the corresponding contingent.